Do politicians' preferences matter for voters' voting decisions? - Matz Dahlberg; Eva Mörk; Pilar Sorribas-Navarro (Uppsala University, Department of Economics, 2011)
Using unique survey data that allows us to observe both voters' and politicians' preferences for local public spending as well as voting decisions, this paper tests if voters typically support parties in which the politicians' preferences are closest to their own. Doing so would be rational for the voters to do if politicians' preferences matter for policy outcomes, as is the case in e.g. the citizen-candidate model. It is found that this is indeed the case. This finding is in line with theoretical models such as the citizen-candidate model arguing that politicians cannot credibly commit to election platforms that differ from their true policy preferences.
urn:nbn:se:uu:diva-154645
Keywords: H71; P16; 330; elections; voting; preferences for public services; Kommunale Ausgaben; Wahlverhalten; Offenbarte Präferenzen; Politiker; Schweden